Biochemical indicators of the organism condition of rats which received high-fat diets with different fatty acid composition - A. P. Levitsky; I. A. Selivanskaya; A. V. Markov; T. I. Pupin (Kazimierz Wielki University, 2020)
Aim. To determine the effects on the body of high-fat diets (HFD) with different fatty acid composition. Methods. Used ordinary sunflower, olive, palm and butter, which were introduced into the feed in an amount of 15 %. Rats were fed for 41 days. Gum, liver, small intestinal mucosa were isolated and blood serum was obtained, which determined the activity of elastase, ALT and alkaline phosphatase, as well as the content of glucose, triglycerides and cholesterol. The activity of elastase, catalase, urease, lysozyme, and MDA content were determined in tissue homogenates. The API index and the degree of dysbiosis were calculated. Results. In rats treated with HFD, elastase, urease, MDA content increased, but lysozyme and catalase activity decreased in all tissues, the API index also decreased, and the degree of dysbiosis increased significantly. Serum triglycerides and cholesterol increased. Stronger pathological changes occurred in rats treated with palm or butter, and the lowest in rats treated with olive oil. Conclusion. HFD causes the development of dysbiosis, decreased levels of antioxidant protection and the development of inflammation, more pronounced with the consumption of fats high in palmitic acid.